Laserspectroscopic studies of bimolecular elementary reaction dynamics in the gas phase - Volpp, Hans-Robert; Wolfrum, Jürgen (Gas phase chemical reaction systems, 1996)
In the present article we give an overview of recent work carried out in our laboratory in order to study microscopic details of bimolecular gas phase reactions at the molecular level using the laser photolysis / laser-induced fluorescence (LP/LEF) “pump-and-probe” technique. In particular, we will focus on the following three- and four-atom reactions: H + O2 → O + OH, H + CO2 ⇌ CO + OH and H + H2O ⇌ H + OH, each of them playing an important role in atmospheric and combustion chemistry. In recent years, these reactions have become prototype systems in the development of full-dimensional quantum mechanical reactive scattering methods and the computation of the necessary accurate ab initio potential energy surfaces. We shall present absolute reactive cross sections and nascent OH product vibrational and rotational fine-structure state distributions, measured over a wide range of collision energies to investigate in detail the influence of reagent translational excitation on reactivity and reaction dynamics. The experimental results allow comparison with quasiclassical and recent quantum mechanical scattering calculations on ab initio potential energy surfaces.